Multi-step process for selecting strategic sourcing options when designing supply chains - Imma Ribas; Amaia Lusa; Albert Corominas (Journal of Industrial Engineering and Management (JIEM), 2021)
Purpose: This paper, devoted to the selection of strategic sourcing options as a part of the supply chain design, aims to provide supply chain designers with guidelines for selecting the best strategic sourcing option for each item (i.e., products, modules, parts and services). Design/methodology/approach: The study is based on a review of the literature on sourcing options, buyer-supplier relationships, factors and criteria to select a sourcing strategy as well as the authors experience in this field. Findings: We propose a multi-step process by considering the three dimensions of the strategic sourcing options (who and how many will make the item; in cases of outsourcing, the kind of relationship between buyer and supplier(s); and where the item is to be made) together with the characteristics of the context, demand and product, and the relevant criteria to evaluate them. Originality/value: The main contributions are the review of the factors and criteria for selecting the best strategic sourcing option for each item (i.e., products, modules, parts and services) as well as the guidelines provided for each step of the process.
Keywords: 650; Strategic sourcing; supply chain design; procurement and production network; outsourcing